Sporadic MM-1 Type Creutzfeldt-Jakob Disease With Hemiballic Presentation and No Cognitive Impairment Until Death: How New NCJDRSU Diagnostic Criteria May Allow Early Diagnosis - Saraceno, Lorenzo; Ricigliano, Vito A. G.; Cavalli, Michele; Cagol, Alessandro; Bosco, Giovanna; Moda, Fabio; Caroppo, Paola; Meola, Giovanni (Frontiers in Neurology, 2018)
Sporadic Creutzfeldt-Jakob disease is the most common human prion disorder. Although associated with heterogeneous clinical phenotypes, its distinctive feature is the presence of a rapidly progressive multidomain cognitive impairment. We describe the atypical case of a patient affected by sporadic Methionine/Methionine type 1 Creutzfeldt-Jakob disease (typically associated with early cognitive decline) who presented with an isolated hemiballic syndrome and no signs of cognitive involvement until death. We review sporadic Creutzfeldt-Jakob disease diagnostic criteria and their updates since their first formulation, highlighting their limitations in clinical diagnostic work-up. Finally, we discuss the recently introduced National Creutzfeldt-Jakob Disease Research and Surveillance Unit diagnostic criteria, suggesting how their application could support an early clinical diagnosis, even in atypical cases, such as the one presented.